2003
DOI: 10.1007/bf03021035
|View full text |Cite
|
Sign up to set email alerts
|

Continuous mixed venous oxygen saturation, not mean blood pressure, is associated with early bupivacaine cardiotoxicity in dogs

Abstract: cSvO(2), but not MBP, is associated with CO changes in bupivacaine-induced cardiac depression during the early period of bupivacaine intoxication. Decrease of MBP with low cSvO(2) observed during the late period might imply severe cardiac depression induced by bupivacaine infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…13 In this study, MAP did not decrease during the bupivacaine infusion, as observed in our previous report. 5 Contrary to another investigation, 7 HR decreased with small doses of bupivacaine, which probably resulted from a reduction of the neurologic and hormonal responses of the anesthetized animals. No evidence of seizure activity was observed, nor sudden increases of HR, MAP, CO and motor movement.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…13 In this study, MAP did not decrease during the bupivacaine infusion, as observed in our previous report. 5 Contrary to another investigation, 7 HR decreased with small doses of bupivacaine, which probably resulted from a reduction of the neurologic and hormonal responses of the anesthetized animals. No evidence of seizure activity was observed, nor sudden increases of HR, MAP, CO and motor movement.…”
Section: Discussioncontrasting
confidence: 63%
“…9,10 The mean electrical axis of the heart and ECG shape are influenced by the properties of the conduction system and cardiac muscle, and this may manifest differently according to different leads of the ECG. Bupivacaine infusion increased ECG intervals 5,11 and decreased the R-wave amplitude in lead II. 6 We assumed that the changes of ECG morphology according to different leads are possible indicators for the early detection of bupivacaine-induced decreases in CO.…”
Section: Résultats : L'axe éLectrique Moyen Du Coeur a éTé Dévié Versmentioning
confidence: 91%
See 2 more Smart Citations
“…3 and its definition can be found in our article. 1 An earlier study showed that a plasma bupivacaine concentration of 1 to 2 µg·mL -1 increased BP and decreased CO. 4 CO does not always decrease with bupivacaine administration. After convulsive doses (1 mg·kg -1 ), CO increases.…”
mentioning
confidence: 98%